A Long-Term and Large-Scale Real-World Study in Taiwan: Efficacy of Target Therapy in Stage IV Colorectal Cancer - Huang, Sheng-Chieh; Lin, Chun-Chi; Teng, Hao-Wei; Lin, Hung-Hsin; Chang, Shih-Ching; Lan, Yuan-Tzu; Wang, Huann-Sheng; Yang, Shung-Haur; Chen, Wei-Shone; Jiang, Jeng-Kai (Frontiers in Oncology, 2022)
CRC is the most commonly diagnosed cancer and the third leading cause of cancer-related death in Taiwan. The aim of this study was to evaluate the efficacy of target therapy in combination with chemotherapy for mCRC in Taiwan. This was a real-world, retrospective, observational study in patients diagnosed with mCRC (N=1583). A total of 792 patients received chemotherapy plus target therapy (anti-EGFR therapy, n=180; anti-VEGF therapy, n=612) and 791 patients who received chemotherapy alone. Overall survival (OS) and progression-free survival (PFS) were examined. For RAS wild-type patients, the median OS (mOS) was 34.3 months in the EGFR L (left-sided colon) group, 27.3 months in the VEGF L group, 18.4 months in VEGF R (right-sided colon) group, and 13.8 months in EGFR R group (P<0.001). Median PFS (mPFS) was 9.8 months in the EGFR L group, 8.9 months in the VEGF L group, 6.8 months in VEGF R group, and 5.8 months in EGFR R group. In patients with a RAS mutation, mOS was 25.4 months in the VEGF L group and 19.4 months in the VEGF R group (P=0.167). Judicious treatment allocation in Taiwanese patients with mCRC can result in an mOS of 34.3 months using cetuximab plus chemotherapy for left-sided tumors. An mOS of 48.5 months can be achieved using cetuximab plus chemotherapy in the neoadjuvant setting in mCRC patients with left-sided tumors. This study expands our understanding of the role of target therapy in improving survival of mCRC patients based on real-world study results.